Use of agrochemicals in potato farming in Pacayas, Cartago, Costa Rica. - Ramírez-Muñoz, Fernando; Fournier-Leiva, María Luisa; Ruepert, Clemens; Hidalgo-Ardón, Carlos (Agronomía Mesoamericana, 2014)
The objective of this work was to produce a diagnostic of the use of pesticides and other agro-chemicals by potato growers in Cartago, Costa Rica. The use of pesticides and fertilizers in potato fields of the Plantón Pacayas Watershed in Cartago, Costa Rica were diagnosed using field surveys, between 2006 and 2009. It was found that, on average, each farmer uses 32.8 kg of pesticide active ingredient per hectare per cycle (kg ai/ha/cycle), in a wide range of 10.9 to 88.3 kg. Weighted average pesticide use per hectare was found to be 42.6 kg ai/ha/cycle and 1879 kg/cycle of formulated fertilizers, representing a relatively high use compared to other intensive crops. The largest group used is fungicides-bactericides with 30 ai, representing 85.7% of all pesticides used, followed by insecticides (25 ai and 11.0%) and herbicides (4 ai and 3.3%). The most widely used pesticide is the fungicide mancozeb, come next by chlorothalonil and propineb; other high-use pesticides are fosetyl aluminum, cartap, methamidophos, endosulfan and paraquat. Unregistered and recognized toxic (acute and chronic toxicity) pesticides are used for potato production. Large area producers of potatoes use a higher quantity of pesticides, but use far less variety than smaller ones. More pesticides and fertilizers are during the rainy season from May to December.